Soviet-party personnel of western regions of USSR in 1944 - 1945 (educational domain) - Eduard Bilous (Cхід, 2013)
The educational level of the Soviet nomenclature of the western regions of the Ukrainian Soviet Republic in the years 1944-1945 is being investigated. The analysis of the research of the phenomenon of the nomenclature of the major Ukrainian scientists such us: M.S. Doroshko, S.V.Kulchitskiy, Y.I. Shapoval, G.V. Kasyanov, L.M. Novokhatko, M.Y. Vygovskiy, R.Pirog, was made. The characteristic features of the local authorities and their influence on the socio-economic and political situation of the Western Ukraine were explained.